Human intelligence - Hunt, Earl B. (Cambridge ; New York : Cambridge University Press, 2011)
'This book is a comprehensive survey of our scientific knowledge about human intelligence, written by a researcher who has spent more than 30 years studying the field. It takes a non-ideological view of a topic in which, too often, writings are dominated by a single theory or social viewpoint. The book discusses the conceptual status of intelligence as a collection of cognitive skills that include, but also go beyond, those skills evaluated by conventional tests; intelligence tests and their analysis; contemporary theories of intelligence; biological and social causes of intelligence; the importance of intelligence in social, industrial, and educational spheres; the role of intelligence in determining success in life, both inside and outside educational settings; and the nature and causes of variations in intelligence across age, gender, and racial and ethnic groups'--Provided by publisher.
The issue of intelligence -- The tests -- On theory -- Psychometric theories -- Taking intelligence beyond psychometrics -- The mechanics of intelligence -- Intelligence and the brain -- The genetic basis of intelligence -- Environmental effects on intelligence -- What use is intelligence? -- The demography of intelligence -- Summary and prospectus.
Includes bibliographical references (p. 453-484) and indexes.
Keywords: Intellect